Dari Teks ke Makna: Teori Interpretasi Paul Ricoeur dan Relevansinya bagi Studi Al-Qur'an - Mumtaz Ibnu Yasa; Muhammad Nurman (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
This study examines Paul Ricoeur's theory of interpretation and explores its relevance to the development of contemporary Qur'anic studies methodology. The research employs a library research approach using descriptive-analytical methods. Primary data are drawn from Ricoeur's major works, while secondary sources consist of scholarly literature on hermeneutics and Qur'anic interpretation. The analysis focuses on four principal concepts in Ricoeur's hermeneutics: symbolic interpretation and textual autonomy, distanciation, the dialectic of explanation and understanding, and appropriation, which are then examined in relation to the methodological principles of the Islamic exegetical tradition. The findings demonstrate that these concepts correspond closely with fundamental principles of Qur'anic exegesis, including the universality of the Qur'anic message, the significance of historical context, methodological validation, and the contextual actualization of Qur'anic teachings. Textual autonomy explains the Qur'an's enduring relevance across different historical and cultural settings, while distanciation enables productive interpretation without compromising textual integrity. The dialectic of explanation and understanding highlights the necessity of integrating linguistic and historical analysis with contextual interpretation, whereas appropriation emphasizes the transformative function of interpretation in the reader's life. This study concludes that Ricoeur's hermeneutics can serve as a dialogical methodological framework that enriches contemporary Qur'anic studies without replacing the foundational principles of 'ulum Al-Qur’an, thereby fostering interpretations that are systematic, contextual, academically accountable, and relevant to contemporary challenges.